Avaliação comparativa da rugosidade superficial e da retenção de placa bacteriana em abutments empregados na implantodontia - Gomes, Camila de Freitas (2006)
The osseointegration success depends on the integrity of the interface between abutment and peri-implant soft tissues. In this region, there is a sealing, which separates the internal and external environment. In order to have this stability it is necessary the realization of soft tissues normal function in an environment without bacteria and contamination inflammatory. Since the titanium abutments are the most user prosthetic resolutions and their sough surfaces accumulate plaque, which may lead to improve mucositis and peri-implantitis. This subject will characterize the superficial roughness of abutments being related to the accumulation of bacterial plaque. Eight patients rehabilitated with overdenture in the lower jaw, using two implants, had received two types of abutments with different surfaces (conventional and polishing) were observed. The average roughness initial and final of abutments had been evaluated through an interferometer the laser, brand UBM, model MICROFOCUS EXPERT IV and the presence of microorganism by means of aerobic and anaerobic bacterial cultures. The initial and final average roughness had remained equal in the conventional group (0,26µm), while that in the polishing components it has increased (0,11µm-0,14µm). A bigger amount of bacterial colonies had been observed in the group of the conventional components if compared with the group of the polishing components. Considering our results, we can conclude that the increase of the roughness contributes directly towards a bigger retention of plaque on the prosthetic components.